Shared phylogeographic patterns and widespread chloroplast haplotype sharing in Eucalyptus species with different ecological tolerances - Nevill, Paul; Després, T.; Bayly, M.; Bossinger, G.; Ades, P. (Springer Verlag, 2014)
We examined the phylogeography of three south-east Australian trees (Eucalyptus delegatensis, Eucalyptus obliqua, and Eucalyptus regnans) with different tolerances, in terms of cold, drought, fire and soil to explore whether species with different ecologies share major phylogeographic patterns. A second aim of this study was to examine geographic patterns of chloroplast DNA (cpDNA) haplotype sharing among the three study species. Trees of E. delegatensis (n = 120), E. obliqua (n = 265) and E. regnans (n = 270) were genotyped with five cpDNA microsatellite markers. The species shared major phylogeographic disjunctions, and common patterns at proposed glacial refugia (generally high haplotype diversity) and areas thought to have been treeless during the Last Glacial Maximum (LGM) (low diversity). Inter-specific sharing of haplotypes was extensive, and fixation of shared, regional haplotypes was more frequent in areas postulated as having been treeless at the LGM. Despite ecological differences, chloroplast microsatellite data suggest the three species have responded to past climatic changes in a similar way, by persisting in multiple, generally common refugia. We suggest that the natural ability of eucalypt species to hybridise with others with quite different or broader ecological tolerances may provide an "insurance policy" for response to rapidly changing abiotic conditions.